Constitutional Court Decision Influence on The Role of Notaries in Legalisation of Marriage Agreements and Third Parties: - - Edenela, Kirana; Busro, Ery Achmad (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
The Constitutional Court Decision Number 69/PUU-XIII/2015 has changed the norms. The agreement is valid from the start of the marriage if the husband or wife do not decide when it takes effect. The notary has additional authority to ratify marriage agreements that conflict with Article 16 (1) UUJN. The research uses qualitative research with normative juridical research, collecting data from laws, books, theses, and journals. The results showed that the third parties who make marriage agreements in the form of a notarial deed, ensuring the contents do not conflict with applicable norms and cannot be changed at will by the husband or wife. The notary is expected to request an inventory list of assets acquired in the marriage bond and make a statement that these assets have never been transacted in any way or form.